Memory impairment in post-COVID-19 syndrome; what is the evidence? - Luciano Luiz Alt; Amanda Delai Bortolini; Bruna Santin Andreis; Caroline Arais Schmidt; Giovana Rugeri; Maria Clara Tonini Pagliarin; Maria Eduarda Dupond Kindel; Maria Fernanda Almeida Costa; Nathália Lorenzoni Costa; Pedro Henrique Sarmento Dariz; Vinícius Grasseli Omizzolo (Journal of Mind and Medical Sciences)
Objectives. Although COVID-19 mainly affects the respiratory system, it can also cause neurological complications like memory impairment, which may be part of post-COVID-19 Syndrome. Identifying these impairments is challenging due to the lack of approaches and limited follow-up. This systematic review aimed to identify the effects of COVID-19 on memory. Methods. Analyzing articles from PubMed, SciELO, and VHL databases, focusing on the relationship between COVID-19 infection and memory impairment. Results. COVID-19 infection was linked to significant declines in memory function. The severity of infection correlated with the intensity of neurological sequelae, particularly memory impairment, with cognitive and executive functions most affected. Recovery in these functions paralleled symptom improvement. Conclusions. Patients often continued to exhibit executive function impairments and cognitive deficits after recovering, complicating the understanding of the underlying pathophysiology.